APPLICATION OF EXPLICIT INSTRUCTION LEARNING MODELS TO IMPROVE STUDENT LEARNING EXPRESSION - Hendra Juliansyah; Johanes Sapri (DIADIK, 2018)
The purpose of this study was to determine the effect of the influence of explicit instruction learning model to improve student learning achievement. The design used in Classroom Action Research (CAR) in class X TBSM 1 There were 36 students consisting of 35 men and 1 woman as respondents in the study. Data collection uses multiple choice objective tests with 4 answer choices. Test questions have been tested to see their validity and reliability. Data analysis using statistical assistance, namely the t test. The results of the study show that there is an influence of explicit instruction learning model to improve student learning achievement. The application of explicit instruction learning models in learning can be applied to other fields of study